EFEKTIVITAS MEDIA TUMBUH COCOPEAT TERHADAP PRODUKSI TANAMAN CABAI RAWIT (Capsicum frutescens L.) DALAM POT - Harahap, Parmanoan (JURNAL AGROPLASMA, 2022)
This study aims to determine the production yield of cayenne papper (capsicum frutescens L.) using cocopeat growing media in pots. The method used in this study was a non-factorial randomized block design (RAK) using cocopeat as a planting medium whit a level of A0: rop soil + goat manure (9 kg/pot + 1 kg/pot), A1 : cocopeat + goat manure (5 kg/pot + 1 kg/pot), A2 : top soil + cocopeat + goat manure ( 5 kg/pot + 5 kg/pot + 1 kg/pot). Based on the results of research that has been carried out, cocopeat planting media 5 kg/pot + goat manure 1 kg/pot is the best combination of planting media from all planting media treatments that have been tested in this tudy, the number of flower the number of productive branches, the number of fruit, and fruit weigh of cayenne pepper. It is recommended to use a maxture of cocopeat an goat manure growing media (A1 treatment) and soak the cocopeat longer than what has been done ( 3 days).Â Key words: cayenneÂ  pepper, cocopeat, produktivity